Comparison of Al speciation and other soil characteristics between meadow, young forest and old forest stands - Dlouhá, Sárka; Borůvka, Lubos; Pavlů, Lenka; Tejnecký, Václav; Drábek, Ondrej (Journal of inorganic biochemistry, 2009)
The aim of this paper is to describe the influence of spruce (Picea abies) afforestation on soil chemical properties, especially on soil acidity and aluminium (Al) mobilization and speciation in soil. For our study we used a unique set of three adjacent plots, including a meadow and two spruce forest stands of different age, in otherwise comparable conditions. The plots were located in the region of Giant Mountains, north-eastern Czech Republic. In general, pH values decreased and Al concentrations increased significantly after afforestation. Speciation of KCl-extractable and water-soluble Al in soil samples was done by means of HPLC/IC method. The concentrations of Al(X)(1+) and Al(Y)(2+) forms (in both extracts) are higher in humic and organically enriched (Bhs) horizons. The highest concentration of Al(3+) in both extracts is in the B horizons of old forest. Generally, in all studied stands majority of Al in aqueous extract is in the Al(X)(1+) form, which indicates that a large amount of mobile Al is bound in organic complexes. It suggests that actual toxicity is rather low. On the other hand, we have proved that majority of KCl-extractable Al exists in Al(3+) form. Thus we can conclude that disturbance of existing equilibrium may cause massive release of highly toxic Al(3+) from soil sorption complex to the soil solution, and consequently it can endanger the whole ecosystem. Moreover, continuous soil acidification accelerated by anthropogenic factors leading to Al mobilization represents a chemical time bomb.
Keywords: Soil Pollutants; látky znečišťující životní prostředí; stromy; hliník; ekosystém; Environmental Pollutants; Environmental Monitoring; Trees; Ecosystem; látky znečišťující půdu; půda; Aluminum; monitorování životního prostředí; Soil